2020
DOI: 10.1088/2053-1591/ab98ca
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial Ni substitution in V85Ni15 by Ti on microstructure, mechanical properties and hydrogen permeability of V-based BCC alloy membranes

Abstract: Vanadium-based alloy membranes with body-centred-cubic (BCC) structure are considered as one of the leading alternatives to Pd-based alloys for hydrogen separation applications due to their lower cost and higher permeability. As permeability and mechanical properties depend on what microstructure can be produced mainly by alloy composition under same processing conditions, the effect of alloy composition on microstructure, mechanical properties and hydrogen permeability has been investigated for the V 85 Ni 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…More specifically, decreased hydrogen solubility and restrained hydride formation are desirable. Experimental studies have shown that hydrogen solubility in transition metal alloys exhibits the following sequence: 13,15 ; adding Ni to V substantially reduces the hydrogen solubility of pure V, improving its resistance to H embrittlement 21,22,23 . Further, Ni, an effective catalytic component, is widely employed in hydrogen storage materials, chemical fuels, and organic chemical synthesis 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, decreased hydrogen solubility and restrained hydride formation are desirable. Experimental studies have shown that hydrogen solubility in transition metal alloys exhibits the following sequence: 13,15 ; adding Ni to V substantially reduces the hydrogen solubility of pure V, improving its resistance to H embrittlement 21,22,23 . Further, Ni, an effective catalytic component, is widely employed in hydrogen storage materials, chemical fuels, and organic chemical synthesis 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, alloying can decrease hydrogen solubility and restrain hydride formation. Experimental studies have shown that hydrogen solubility in transition metal alloys exhibits the following sequence: V–Ti > V–Cr > V–Mn > V–Fe > V–Co > V–Ni [ 11 , 14 ]; Ni doping substantially reduces the hydrogen solubility of pure V, improving its resistance to H embrittlement [ 22 , 23 , 24 ]. Further, Ni, an effective catalytic component, is widely employed in hydrogen storage materials, chemical fuels, and organic chemical synthesis [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%